Transformation of atenolol, metoprolol, and carbamazepine in soils: The identification, quantification, and stability of the transformation products and further implications for the environment - Koba, Olga; Golovko, Oksana; Kodešová, Radka; Klement, Aleš; Grabic, Roman (Environmental pollution (Barking, Essex, 2016)
Pharmaceuticals are a large group of substances that have been recognized as environmental contaminants in recent years. Research on the pharmaceutical fate in soils is currently limited or missing. In this study, three pharmaceuticals (atenolol (ATE), carbamazepine (CAR), and metoprolol (MET)) were introduced to soils and exposed for 61 day under aerobic conditions. Thirteen different soils were used in the study to increase the understanding of pharmaceutical behaviour in the soil matrix. Ten metabolites were detected and tentatively identified. Some of them, such as atenolol acid (AAC), carbamazepine 10,11-epoxide (EPC), 10,11-dihydrocarbamazepine (DHC), trans-10,11-Dihydro-10,11-dihydroxy carbamazepine (RTC), and metoprolol acid (MAC), were consequently confirmed using commercial reference standards. It was concluded that the aerobic conditions of the experiment determined the pharmaceutical degradation pathway of studied compounds in the soils. The different amounts/rates and degradation of the transformation products can be attributed to differences in the soil properties. ATE degraded relatively quickly compared with CAR, whereas MET degradation in the soils was unclear. The persistence of CAR and its metabolites, in combination with low CAR sorption, enable the transportation of CAR and its metabolites within soils and into the ground water. Thus, CAR may cause adverse effects on the environment and humans.
Keywords: Carbamazepine; Liquid chromatography high resolution mass spectrometry; atenolol; Metabolites; metoprolol; látky znečišťující půdu; Atenolol; Soil; Soil Pollutants; Soil compartment; podzemní voda; karbamazepin; lidé; Groundwater; Humans; Metoprolol; Degradation; Pharmaceuticals; půda